Nordihydroguaiaretic acid impairs prostate cancer cell migration and tumor metastasis by suppressing neuropilin 1 - Li, Xin (Oncotarget, 2016)
Tumor metastasis is a major cause leading to the deaths of cancer patients. Nordihydroguaiaretic acid (NDGA) is a natural product that has been demonstrated to show therapeutic values in multiple diseases. In this study, we report that NDGA can inhibit cell migration and tumor metastasis via a novel mechanism. NDGA suppresses NRP1 function by downregulating its expression, which leads to attenuated cell motility, cell adhesion to ECM and FAK signaling in cancer cells. Moreover, due to its cross-cell type activity on NRP1 suppression, NDGA also impairs angiogenesis function of endothelial cells and fibronectin assembly by fibroblasts, both of which are critical to promote metastasis. Based on these comprehensive effects, NDGA effectively suppresses tumor metastasis in nude mice model. Our findings reveal a novel mechanism underlying the anti-metastasis function of NDGA and indicate the potential value of NDGA in NRP1 targeting therapy for selected subtypes of cancer.